PRECAUTIONARY AND PROTECTION MEASURES IN FAMILY VIOLENCE PROCESSES BY THE PUBLIC MINISTRY AND FAMILY COURTS OF THE CITY OF PUNO IN THE YEARS 2010-2011 - Carmen A. Ccaso Gutierrez (2019)
This research work is entitled: "PRECAUTIONARY AND PROTECTIVE MEASURES IN FAMILY VIOLENCE PROCESSES BY THE PUBLIC MINISTRY AND FAMILY COURTS OF THE CITY OF PUNO IN THE YEARS 2010-2011", framed by current regulations, between they Law No. 26260 "Law on Protection against Family Violence", and its objective is to determine whether the precautionary and protection measures issued by the Public Ministry and confirmed by the family courts of the city of Puno in the processes of Family violence are timely and effective, as the main variables we have the precautionary and protective measures in the processes of family violence and the competent Bodies, with the purpose of reducing family violence in the city of Puno, whose purpose is transcendental, because as it is public knowledge in our country family violence is alarming because of its multiple manifestations that put the unit at risk family, and therefore it is believed that this investigation is justified. The results presented here are that protection measures are attitudes that the State takes into account in order to protect victims of family violence, which must tend to be effective, the lack of drastic measures for non-compliance with these measures. prevents the cessation of violence, also these cases of family violence must be considered in the Andean communities or indigenous peoples so that in a self-determination way they solve their problems and new protection measures must be dictated in accordance with our reality.